2022
DOI: 10.3390/pathophysiology29020013
|View full text |Cite
|
Sign up to set email alerts
|

Hsa-Mir-320c, Hsa-Mir-200c-3p, and Hsa-Mir-449c-5p as Potential Specific miRNA Biomarkers of COPD: A Pilot Study

Abstract: Chronic obstructive pulmonary disease (COPD) is a chronic inflammatory disease commonly induced by cigarette smoke. The expression of miRNAs can be altered in patients with COPD and could be used as a biomarker. We aimed to identify a panel of miRNAs in bronchoalveolar lavage (BAL) to differentiate COPD patients from smokers and non-smokers with normal lung function. Accordingly, forty-five subjects classified as COPD, smokers, and non-smokers (n = 15 per group) underwent clinical, functional characterization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…These contrasting effects in different compartments and diseases suggest that miRNA expression might depend on specific cell type activation within a particular context. Regarding the up-regulation of miR-449c-5p, our results align with a study in COPD demonstrating a higher expression of this miRNA in BAL-derived extracellular miRNAs of COPD patients compared to smokers and nonsmokers [37]. Similarly, miR-10a-5p was found to be higher in bronchial epithelial cells from patients with asthma and COPD compared to controls [38].…”
Section: Discussionsupporting
confidence: 89%
“…These contrasting effects in different compartments and diseases suggest that miRNA expression might depend on specific cell type activation within a particular context. Regarding the up-regulation of miR-449c-5p, our results align with a study in COPD demonstrating a higher expression of this miRNA in BAL-derived extracellular miRNAs of COPD patients compared to smokers and nonsmokers [37]. Similarly, miR-10a-5p was found to be higher in bronchial epithelial cells from patients with asthma and COPD compared to controls [38].…”
Section: Discussionsupporting
confidence: 89%
“…MiR‐449c‐5p was remarkably increased in palatal cells 21 . It was a potential therapeutical target for chronic obstructive pulmonary disease (COPD), which was proved by a pilot study 22 . In nasopharyngeal carcinoma (NPC), miR‐449c‐5p was differently expressed 23 .…”
Section: Discussionmentioning
confidence: 98%
“… 21 It was a potential therapeutical target for chronic obstructive pulmonary disease (COPD), which was proved by a pilot study. 22 In nasopharyngeal carcinoma (NPC), miR‐449c‐5p was differently expressed. 23 The research articles indicated that miR‐449c‐5p regulated the STAT6 signalling pathway of acute cerebral infarction (ACI).…”
Section: Discussionmentioning
confidence: 99%